Exploring the molecular mechanism of action of Polygonum capitatum Buch-Ham. ex D. Don for the treatment of bacterial prostatitis based on network pharmacology and experimental verification. (12th June 2022) - Fan, Shanshan; Huang, Yuxing; Zuo, Xurui; Li, Ziqiang; Zhang, Liyan; Tang, Jingwen; Lu, Liping; Huang, Yuhong
Abstract: Ethnopharmacology relevance: Polygonum capitatum Buch-Ham. ex D. Don (CNPC2009), a traditional Miao-national herbal medicine, has been widely used with considerable therapeutic efficacy in the treatment of various urologic disorders including prostatitis. However, the molecular mechanism of action (MOA) remains unclear. Aim of the study: In this study, UPLC-Q-Exactive-MS and Network pharmacological methods were used to explore the underlying molecular MOA of Polygonum capitatum Buch-Ham. Ex D. Don ( P.capitatum ) for the treatment bacterial prostatitis (BP). Materials and methods: The UPLC-Q-Exactive-MS technique was used to identify the chemical components of P. capitatum . Databases such as SwissTargetPrediction, Gene Cards, and OMIM were used to predict the targets of P. capitatum for the treatment of BP. The Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) was used to analyze the protein-protein interaction (PPI) and construct a PPI network, and the Metascape was used for Gene Ontology (GO) term enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. In addition, experimental treatment of Escherichia coli (E.coli)-induced BP was verified. Results: A total of 31 molecular components were identified by UPLC-Q-Exactive-MS. Network pharmacology revealed that P. capitatum may act on the AKT1, PI3K, MTO, EGFR and other targets through active components such as Gallic acid, Quercetin, Luteolin, Protocatechuic Acid, Kaempferol and thereby regulate PI3K-AKT, ErbB, AMPK, HIF-1, and other signaling pathways to intervene in the pathological mechanism of BP. Verification through experimental results showed that compared with the model group, treatment with P. capitatum could significantly inhibit bacterial growth in prostate tissues, lowered the prostate index, down-regulated the levels of inflammatory mediators(IL-1β, IL-6, and TNF-α) in prostate tissues, and down-regulate the protein expression and mRNA expression levels of AKT and PI3K. Conclusion: This study preliminarily revealed the MOA of P. capitatum for treating BP with multiple components, multiple targets, and multiple pathways, especially affecting the PI3K-AKT signaling pathways. Graphical abstract: Image 1 Highlights: Polygonum capitatum is a traditional Miao's Medicinal plant for prostatitis. Polygonum capitatum inhibited the prostatitis rat bacterial growth and expression of proinflammatory cytokines. Polygonum capitatum mediates anti-inflammatory effects through the PI3K-AKT pathway.